A polyurethane material based on urea-based pyrimidinone and lithium ion synergistic coordination and a preparation method thereof
Patent Information
- Application Number
- CN202610856990.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-15
AI Technical Summary
这类永久交联虽然在短期内能提供较高的强度和弹性,却难以在导电性、损伤修复和重复加工等前沿需求上取得平衡
[0024] (1) The polyurethane molecular chain of the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions of the present invention is grafted with UPy units, and the UPy units and lithium salt together construct a multi-layer dynamic interaction network. The UPy units can form a strong dimer structure through self-recognizing quadruple hydrogen bonds, and these dimers act as high-strength non-covalent crosslinking points; at the same time, lithium ions coordinate with the carbonyl oxygen, pyrimidin nitrogen and other coordination sites on the UPy ring to form metal-ligand coordination, and generate ion-dipole interactions with Lewis base groups such as ether oxygen in the soft segment. The synergistic effect of hydrogen bonds and coordination bonds significantly amplifies the non-covalent bonding ability between molecular chains. At the same time, the reversibility of dynamic bonds also endows the material with significant energy dissipation ability, and can greatly improve the mechanical properties of polyurethane through continuous bond dissociation and recombination.
Smart Images

Figure CN122404659B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane materials technology, and in particular to a polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions and its preparation method. Background Technology
[0002] Polyurethane, as a highly adaptable polymer material, has secured a core position in coatings, elastomers, adhesives, and foam plastics due to its excellent mechanical properties, chemical resistance, and processing versatility. However, with emerging technologies such as flexible electronics, intelligent drives, and self-healing coatings demanding integrated "high mechanical load-bearing capacity and ion conduction" functions, traditional polyurethanes relying solely on covalent crosslinking or simple hydrogen bond networks are no longer sufficient.
[0003] Furthermore, the traditional structure of polyurethane relies primarily on irreversible covalent bond networks to maintain its mechanical integrity. While this type of permanent crosslinking can provide high strength and elasticity in the short term, it is difficult to achieve a balance between current demands for conductivity, damage repair, and reprocessing. In particular, when covalent bonds break under long-term dynamic loads or excessive deformation, it can lead to permanent damage and performance degradation of the material. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a polyurethane material based on the synergistic coordination of ureidopyrimidinone (UPy) and lithium ions. This material no longer relies solely on isolated ionic bonds, but instead grafts UPy motifs capable of self-association to form quadruple hydrogen bonds onto the polyurethane chain and synergistically complexes them with lithium salts to construct a dynamic network integrating hydrogen bonds and metal-ligand coordination.
[0005] A further technical problem to be solved by the present invention is to provide a method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A polyurethane material based on the synergistic coordination of ureidinone and lithium ions is disclosed. Ureidinone units are grafted onto the polyurethane molecular chain, and the ureidinone units and lithium salt together construct a multi-layered dynamic interaction network. The ureidinone units can form a dimer structure as high-strength non-covalent crosslinking points through self-recognized quadruple hydrogen bonds. The lithium ions in the lithium salt undergo metal-ligand coordination with the coordination sites on the ureidinone and generate ion-dipole interactions with Lewis base groups.
[0008] The polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions forms a microphase separation structure in its molecular structure, which includes a hard phase and a soft phase.
[0009] The hard phase is a ureidopyrimidinone-lithium ion aggregate, and the hard phase is a multifunctional nanodomain with both rigidity and conductivity; the soft phase is a polyether or polyester segment, and the soft phase is a continuous channel for lithium ion transport.
[0010] The above-mentioned method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions includes the following steps:
[0011] S1: Add a first chain extender to the polyurethane prepolymer to carry out a first chain extension reaction; wherein the first chain extender is a diamine chain extender or a diol chain extender, and the molar ratio of the first chain extender to the polyol in the polyurethane prepolymer is (1~2):4; the reaction temperature of the first chain extension reaction is 60-100℃, and the reaction time is 1h~12h.
[0012] S2: After the first chain extension reaction is completed, a second chain extender is added to carry out a second chain extension reaction; wherein the second chain extender is ureidopyrimidinone, and the molar ratio of the second chain extender to the polyol in the polyurethane prepolymer is (1~3):4; the reaction temperature of the second chain extension reaction is 60-100℃, and the reaction time is 3h~12h;
[0013] S3: After the second chain extension reaction is completed, lithium salt is added to carry out the reaction; wherein the molar ratio of the second chain extender to lithium salt is 1:1~3; the reaction temperature in step S3 is 60-100℃, and the reaction time is 3h~12h.
[0014] S4: After the reaction is completed, the reaction product obtained in step S3 is subjected to film formation and drying treatment to obtain a polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions.
[0015] The first chain extender is adipic acid dihydrazide.
[0016] The second chain extender is 1-(6-(3-(1,3-dihydroxy-2-methylprop-2-yl)ureido)hexyl)-3-(4-methyl-6-oxo-1,6-dihydropyrimidin-2-yl)urea.
[0017] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0018] Steps S1, S2, and S3 are all carried out under the condition of an inert reactive gas.
[0019] In step S4, the drying temperature is 60℃~100℃ and the drying time is 24h~72h.
[0020] When the first chain extender, the second chain extender, or the lithium salt is a solid, the solid is dissolved first and then added to the corresponding reaction system.
[0021] The polyurethane prepolymer in step S1 is prepared through the following steps:
[0022] Polyurethane prepolymer is obtained by mixing polyol, diisocyanate and solvent, adding an appropriate amount of catalyst (0.01%-1% relative to the total mass of reactants) and carrying out a prepolymerization reaction.
[0023] The beneficial effects of this invention are as follows:
[0024] (1) The polyurethane molecular chain of the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions of the present invention is grafted with UPy units, and the UPy units and lithium salt together construct a multi-layer dynamic interaction network. The UPy units can form a strong dimer structure through self-recognizing quadruple hydrogen bonds, and these dimers act as high-strength non-covalent crosslinking points; at the same time, lithium ions coordinate with the carbonyl oxygen, pyrimidin nitrogen and other coordination sites on the UPy ring to form metal-ligand coordination, and generate ion-dipole interactions with Lewis base groups such as ether oxygen in the soft segment. The synergistic effect of hydrogen bonds and coordination bonds significantly amplifies the non-covalent bonding ability between molecular chains. At the same time, the reversibility of dynamic bonds also endows the material with significant energy dissipation ability, and can greatly improve the mechanical properties of polyurethane through continuous bond dissociation and recombination.
[0025] (2) The introduction of lithium ions not only enhances the stability of the cross-linked network, but also provides an efficient ion conduction path, enabling the originally insulating polyurethane matrix to have intrinsic ionic conductivity, thus forming a polyurethane elastomer that integrates load bearing and electrical conduction.
[0026] (3) Compared with common single-type ion crosslinking systems, the directional aggregation of UPy and the lithium salt enrichment region synergistically induce a defined microphase separation structure. The hard phase domains are rich in UPy-lithium ion aggregates, serving as multifunctional nanodomains with both rigidity and conductivity; the soft phase maintains the high flexibility of the polyether or polyester segments, while also serving as a continuous channel for lithium ion transport. This structure is similar to a design that integrates strength and conductivity optimization at the molecular level. By changing the UPy grafting density, lithium salt concentration, and anion type, the mechanical properties and ionic conductivity can be systematically controlled, thereby freely balancing the strength, ductility, and conductivity of the material within a wide window.
[0027] (4) The polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions of the present invention has adjustable mechanical properties, such as high strength, high toughness and exceptional stretchability, film-forming properties of polymer materials and excellent ionic conductivity of ionic conductors.
[0028] (5) The polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions of this invention can be widely applied in emerging fields such as flexible and stretchable electronic devices, self-powered sensors, biomimetic ionic skin, elastic electrolytes for all-solid-state batteries, and haptic feedback modules for soft robots. Its design concept provides a new path for simultaneously achieving mechanical reinforcement and functional implantation, and has important implications for the development of next-generation multifunctional integrated polyurethane materials. Attached Figure Description
[0029] Figure 1 This is a synthetic route diagram of a polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions, as described in Example 1 of the present invention.
[0030] Figure 2 The images show the Fourier transform infrared (FTIR) spectra of the polyurethane materials prepared in Examples 1 to 3 and Comparative Example 1 of this invention.
[0031] Figure 3 The stress-strain curves are for the polyurethane materials prepared in Examples 1 to 3 and Comparative Example 1 of the present invention.
[0032] Figure 4 The stress-strain curves of the polyurethane materials prepared in Examples 2, 4 and 5 of the present invention are shown.
[0033] Figure 5 The AC impedance spectroscopy curve of the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions prepared in Example 2 of the present invention. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0035] This invention proposes that introducing ionic groups into the molecular chain and constructing coordination bonds in polyurethane is an important strategy to overcome limitations.
[0036] The core characteristic of coordination-bonded polyurethanes is the introduction of metal ions, which form strong physical crosslinks with coordination nodes. These ionic clusters not only act as both rigid fillers and crosslinking points, enhancing tensile strength and toughness, but also impart a certain degree of ionic conductivity due to the dynamic characteristics of ion movement. Because of the microphase separation of hard and soft segments, ionic groups tend to aggregate in the hard phase domain, with the hard segments providing strength and the soft segments maintaining flexibility and elasticity. By controlling the type, content, and distribution of ionic groups, the mechanical and electrical properties of the polymer can be adjusted within a certain range. However, relying solely on ionic cluster crosslinking often faces an inherent contradiction between crosslinking density and chain motion freedom: excessively high ion content makes the material too soft, resulting in low strength, while excessively low content sacrifices ionic conductivity. Simultaneously, the energy dissipation mechanism of traditional polyurethanes is relatively simple, making it impossible to establish a multi-level relaxed dynamic bond system to balance high modulus and high ductility.
[0037] This invention provides a novel functional polyurethane material co-coordinated with ureidopyrimidinone (UPy) and lithium ions. Instead of relying solely on isolated ionic bonds, this material grafts UPy motifs capable of self-association to form quadruple hydrogen bonds onto the polyurethane chain and co-complexes them with lithium salts, constructing a dynamic network integrating hydrogen bonds and metal-ligand coordination. UPy dimers act as high-strength, directional supramolecular crosslinking points; while lithium ions simultaneously coordinate with the carbonyl oxygen and pyrimidine nitrogen on the UPy ring and form ion-dipole interactions with the soft-segment ether oxygen. The bond energies and relaxation times of these two types of dynamic bonds exhibit hierarchical differences, allowing them to open sequentially under stress and dissipate energy at different scales, forming a hierarchical "sacrificial bond" mechanism. By changing the UPy grafting density and lithium salt concentration, the ratio and strength of these two non-covalent crosslinks can be systematically controlled, thereby flexibly adjusting the temporal hierarchy of energy dissipation within the material and overcoming the performance bottleneck of single-mode crosslinking.
[0038] Based on this synergistic crosslinking network, the lithium-ion coordinated UPy polyurethane of this invention exhibits significantly superior overall performance compared to traditional ionic polyurethanes and pure UPy hydrogen-bonded systems. Compared to hydrogen-bonded UPy elastomers without lithium ions, the introduction of lithium coordination not only greatly enhances the stability and reversible energy dissipation capacity of physical crosslinking, resulting in a significant increase in tensile strength, tear toughness, and ductility, but also allows lithium ions to form efficient ion transport pathways, endowing the material with intrinsic ionic conductivity and achieving the integration of mechanical load-bearing and ion transport functions. Simultaneously, the microphase separation structure synergistically induced by UPy directional aggregation and lithium salt enrichment also significantly improves the material's thermal stability and solvent resistance. Therefore, the UPy-lithium-ion coordinated polyurethane provided by this invention possesses tunable mechanical properties—such as high strength, ultra-high toughness, and exceptional stretchability—as well as excellent ionic conductivity, laying the foundation for the development of next-generation multifunctional integrated polyurethane elastomers.
[0039] The preparation method of the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions of the present invention includes the following steps:
[0040] Part 1: Synthesis of polyurethane prepolymers.
[0041] Select polyester or polyether polyols (molecular weight range: 1000~3000) and mix them in a three-necked flask. Stir and dry them in an oil bath at 100~150℃ under a N2 atmosphere.
[0042] Next, after the above mixture has cooled to 60~100℃, add an equivalent amount of diisocyanate (selectable types: hexamethylene diisocyanate (HDI) / isophorone diisocyanate (IPDI) / diphenylmethane diisocyanate (MDI) / 4,4'-dicyclohexylmethane diisocyanate (HMDI)), and measure a certain amount of organic solvent (selectable solvents: N,N-dimethylformamide (DMF) / N,N-dimethylacetamide (DMAc) / N-methylpyrrolidone (NMP) is mixed and added to a reaction flask, along with a certain amount of catalyst (selectable catalysts include amine catalysts and organometallic catalysts. Amine catalysts are generally tertiary amine salts, such as N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, triethylamine, N,N-dimethylbenzylamine, etc.; organometallic catalysts include dibutyltin dilaurate, stannous isooctanoate, zinc isooctanoate, bismuth isooctanoate, etc.). The reaction temperature is 80℃, and the reaction is carried out in a N2 atmosphere for 2-5 hours to obtain a polyurethane prepolymer.
[0043] Part 2: Preparation of polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions.
[0044] S1: Add an appropriate amount of diamine-based chain extender or diol-based first chain extender to the polyurethane prepolymer synthesized in the first part to carry out the first chain extension reaction; the first chain extenders that can be selected include: adipate dihydrazide, 4,4'-diaminodicyclohexylmethane, 4,4'-diaminobiphenyl, 1,4-butanediol, 4,6-dihydroxypyrimidine, and 2,2,3,3-tetrafluoro-1,4-butanediol. The reaction temperature of the first chain extension reaction is 60-100℃, and the reaction is carried out under a N2 atmosphere for 1-12 hours. If the chain extender is solid, an appropriate amount of organic solvent needs to be added, and the reaction should be ultrasonically treated until the solid chain extender is completely dissolved, and then the dissolved mixture is added dropwise to the reaction flask.
[0045] S2: After the first chain extension reaction is completed, a certain amount of a second chain extender is added to carry out a second chain extension reaction. Suitable second chain extenders include: 5,6-diamino-1,10-phenanthroline, 1-(6-(3-(1,3-dihydroxy-2-methylpropyl-2-yl)ureo)hexyl)-3-(4-methyl-6-oxo-1,6-dihydropyrimidin-2-yl)urea, 4,4'-diamino-2,2'-bipyridine, 4,4'-((1,10-phenanthroline-4,7-diyl)bis(oxo)diphenylamine, and dimethylglyoxime. The reaction temperature for the second chain extension reaction is 60-100℃, and the reaction is carried out under a N2 atmosphere for 3-12 hours. If the second chain extender is a solid, an appropriate amount of organic solvent needs to be added, and the mixture should be sonicated until the solid chain extender is completely dissolved. The dissolved mixture is then added dropwise to the reaction flask.
[0046] S3: After the second chain extension reaction is completed, lithium salt is added to react and obtain the reaction product. The reaction temperature is 60-100℃, and the reaction is carried out under a N2 atmosphere for 3-12 hours. Suitable lithium salts include: lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, and lithium hexafluorophosphate. If the lithium salt is solid, an appropriate amount of organic solvent needs to be added, and the mixture should be sonicated until the solid chain extender is completely dissolved before adding the dissolved mixture dropwise into the reaction flask.
[0047] S4: After the reaction is complete, pour the reaction product obtained in step S3 into a polytetrafluoroethylene mold and vacuum dry it at 60℃~100℃ for 24h~72h to remove residual solvent and obtain a polyurethane elastomer film.
[0048] In the raw materials required for the synthesis of polyurethane in this invention, the preferred molar ratio of polyester polyol: diisocyanate: first chain extender: second chain extender is 4:8:(1~2):(3~1), and the preferred molar ratio of the second chain extender to lithium salt is 1:(1~3).
[0049] Preferably, the first chain extender, the second chain extender, and the lithium salt solution are added dropwise.
[0050] Example 1:
[0051] Figure 1 This is a synthetic route diagram for the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions, as described in Example 1 of the present invention. See also... Figure 1 The preparation method of polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions specifically includes the following steps:
[0052] Part 1: Synthesis of polyurethane prepolymers.
[0053] (1) Weigh 4 mmol, 8.0 g of polycarbonate diol (PCDL-2000) with a molecular weight of 2000 g / mol and 20 mL of DMF and mix them in a three-necked flask. Dry the mixture under oil bath conditions at 120 °C and N2 atmosphere for 120 min.
[0054] (2) Next, after the temperature of the mixture obtained in step (1) is cooled to 80°C, 20 mL of DMF is measured as solvent, 8 mmol and 1.78 g of IPDI (molecular weight of 222.29 g / mol) are weighed and added dropwise to a three-necked flask, and 0.02 g of catalyst DBTDL is added dropwise. The prepolymerization reaction is carried out under oil bath conditions at 80°C and N2 atmosphere for 3 h, and isocyanate-terminated polyurethane prepolymer is obtained.
[0055] Part 2: Preparation of polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions.
[0056] S1: The first chain extender solution is added dropwise to the polyurethane prepolymer prepared in the first part to carry out the first chain extension reaction. The reaction conditions for the first chain extension reaction are an oil bath environment at 80°C, stirring under N2 atmosphere, and a reaction time of 5 hours. The first chain extender solution is prepared by the following steps: 2 mmol of the first chain extender, adipic acid dihydrazide (ADH), in solid form is weighed, and 7 mL of solvent DMF is measured. The solid ADH is dissolved in the solvent DMF and ultrasonicated until completely dissolved to obtain the first chain extender solution.
[0057] The structural formula of the reaction product obtained in step S1 is as follows:
[0058] ;
[0059] S2: After the first chain extension reaction is completed, the second chain extender solution is added dropwise to the reaction system obtained in step S1 to carry out the second chain extension reaction. The reaction conditions for the second chain extension reaction are an oil bath environment at 60℃, stirring under N2 atmosphere, and a reaction time of 5h. The second chain extender solution is prepared by the following steps: 2 mmol of the second chain extender 1-(6-(3-(1,3-dihydroxy-2-methylpropyl-2-yl)ureoyl)hexyl)-3-(4-methyl-6-oxo-1,6-dihydropyrimidin-2-yl)urea (UPy-AMPD) in powder form is weighed, and 16 mL of solvent DMF is measured. The two are mixed and ultrasonically treated until completely dissolved to obtain the second chain extender solution.
[0060] The reaction products obtained in step S2 are as follows:
[0061] ;
[0062] S3: After the second chain extension reaction is completed, a lithium salt solution is added to the reaction system of step S2 to obtain the reaction product. The reaction conditions for step S3 are an oil bath environment at 60°C, stirring under a N2 atmosphere, and a reaction time of 5 hours. The lithium salt solution used in step S3 is prepared by the following steps: 2 mmol of powdered lithium bis(trifluoromethanesulfonyl)imide lithium (LiTFSI) is weighed, and 12 mL of solvent DMF is measured. The two are mixed and ultrasonically treated until completely dissolved.
[0063] The reaction product obtained in step S3 contains both Li-UPy coordination units and UPy dimers; the structural formula of the Li-UPy coordination unit is as follows:
[0064] ;
[0065] The structural formula of UPy dimer is as follows:
[0066] ;
[0067] S4: After the reaction is complete, the reaction product obtained in step S3 is poured into a polytetrafluoroethylene mold and dried under vacuum at 80°C for 48 hours to remove residual solvent. The sample from Example 1 was named HPU2-1:1.
[0068] Example 2:
[0069] The preparation method of Example 2 is basically the same as that of Example 1, except that the lithium salt solution used in step S3 is prepared by the following steps: weigh 4 mmol of powdered lithium salt bis(trifluoromethanesulfonyl)imide lithium, and at the same time measure 23 mL of solvent DMF, mix the two, and sonicate until completely dissolved.
[0070] The sample in Example 2 was named HPU2-1:2.
[0071] Example 3:
[0072] The preparation method of Example 3 is basically the same as that of Example 1, except that the lithium salt solution used in step S3 is prepared by the following steps: 6 mmol of powdered lithium salt bis(trifluoromethanesulfonyl)imide lithium is weighed, and 35 mL of solvent DMF is measured. The two are mixed and ultrasonically treated until completely dissolved.
[0073] The sample in Example 3 was named HPU2-1:3.
[0074] Comparative Example 1:
[0075] The first part of Comparative Example 1 is the same as that of Example 1.
[0076] Part Two: Preparation of Polyurethane Materials
[0077] (1) The first chain extender solution is added dropwise to the polyurethane prepolymer prepared in the first part to carry out the first chain extension reaction. The reaction conditions for the first chain extension reaction are an oil bath environment at 80°C, stirring under N2 atmosphere, and a reaction time of 5h. The first chain extender solution is prepared by the following steps: 2 mmol of the first chain extender in solid form, adipic acid dihydrazide (ADH), is weighed, and 7 mL of solvent DMF is measured. The solid ADH is dissolved in the solvent DMF and ultrasonically treated until completely dissolved to obtain the first chain extender solution.
[0078] (2) After the first chain extension reaction is completed, the second chain extender solution is added dropwise to the reaction system obtained in step (1) to carry out the second chain extension reaction. The reaction conditions for the second chain extension reaction are an oil bath environment at 60°C, stirring under N2 atmosphere, and a reaction time of 5h. The second chain extender solution is prepared by the following steps: 2 mmol of the second chain extender 1-(6-(3-(1,3-dihydroxy-2-methylpropyl-2-yl)ureoyl)hexyl)-3-(4-methyl-6-oxo-1,6-dihydropyrimidin-2-yl)urea (UPy-AMPD) in powder form is weighed, and 16 mL of solvent DMF is measured at the same time. The two are mixed and ultrasonically treated until completely dissolved to obtain the second chain extender solution.
[0079] (3) After the reaction is complete, the reaction product obtained in step (2) is poured into a polytetrafluoroethylene mold and dried under vacuum at 80°C for 48 hours to remove residual solvent. The sample of Comparative Example 1 was named HPU2.
[0080] Example 4:
[0081] The preparation steps of Example 4 are basically the same as those of Example 1.
[0082] The difference is:
[0083] (1) The first chain extender solution used in step S1 of Part 2 is prepared by the following steps: Weigh 1 mmol of solid first chain extender ADH, and at the same time measure 11 mL of solvent DMF, dissolve the solid ADH in solvent DMF, and sonicate until completely dissolved.
[0084] (2) The second chain extender solution used in step S2 of the second part is prepared by the following steps: Weigh 1 mmol of the second chain extender UPy-AMPD in powder form, and measure 8 mL of solvent DMF. Mix the two and sonicate until completely dissolved.
[0085] (3) The lithium salt solution used in step S3 of Part 2 is prepared by the following steps: Weigh 2 mmol of powdered lithium salt LiTFSI and measure 12 mL of solvent DMF. Mix the two and sonicate until completely dissolved.
[0086] The sample in Example 4 was named HPU1-1:2.
[0087] Example 5:
[0088] The preparation steps of Example 5 are basically the same as those of Example 1.
[0089] The difference is:
[0090] (1) The first chain extender solution used in step S1 of the second part is prepared by the following steps: weigh 1 mmol of solid first chain extender ADH, and at the same time measure 4 mL of solvent DMF, dissolve the solid ADH in solvent DMF, and sonicate until completely dissolved.
[0091] (2) The second chain extender solution used in step S2 of the second part is prepared by the following steps: Weigh 3 mmol of the second chain extender UPy-AMPD in powder form, and measure 24 mL of solvent DMF. Mix the two and sonicate until completely dissolved.
[0092] (3) The lithium salt solution used in step S3 of Part 2 is prepared by the following steps: weigh 6 mmol of powdered lithium salt LiTFSI and measure 35 mL of solvent DMF. Mix the two and sonicate until completely dissolved.
[0093] The sample in Example 5 was named HPU3-1:2.
[0094] The characterization analysis of Examples 1 to 5 and Comparative Example 1 is as follows:
[0095] Figure 2 These are Fourier transform infrared (FTIR) spectra of the polyurethane materials prepared in Examples 1 to 3 and Comparative Example 1 of the present invention. Figure 2 The results show that Figure 2 1738cm -1 The stretching vibration peak at 1240 cm⁻¹ belongs to the carbonyl group (-C=O-) in the urethane (-NHCOO-) group. -1 The characteristic peak at 3360 cm⁻¹ is the stretching vibration peak of the -CO- portion of the urethane (-NHCOO-) group, while the peak at 3360 cm⁻¹ is the stretching vibration peak of the -CO- portion of the urethane (-NHCOO-) group. -1 The characteristic peak at 2260-2280 cm⁻¹ is the stretching vibration peak of the imino group (-NH⁻). Simultaneously, the peak at 2260-2280 cm⁻¹ is also present. -1 The absence of a vibrational peak corresponding to -NCO indicates complete reaction of the diisocyanate and successful preparation of the polyurethane material. It is noteworthy that, compared to HPU2 in Comparative Example 1, Examples 1 to 3 show vibrations at 1150-1200 cm⁻¹. -1A CF stretching vibration region appeared between them, which belongs to the trifluoromethyl group in LiTFSI. The presence of this region strongly proves the successful introduction of LiTFSI.
[0096] To effectively evaluate the mechanical properties of the prepared polyurethane materials, stress-strain curve tests were performed on all samples from the examples and comparative examples. The test standard was GB / T 1040-2006, the test speed was 100 mm / min, and the test environment was 25℃.
[0097] Figure 3 The stress-strain curves are for the polyurethane materials prepared in Examples 1 to 3 and Comparative Example 1 of the present invention. Figure 4 The stress-strain curves of the polyurethane materials prepared in Examples 2, 4, and 5 of this invention are shown. The mechanical property test results of Examples 1 to 5 and Comparative Example 1 are shown in Table 1.
[0098] Table 1. Mechanical property test results of Examples 1 to 5 and Comparative Example 1
[0099]
[0100] Depend on Figure 3 As shown in Table 1, compared to HPU2 in Comparative Example 1, the strength and toughness of polyurethane were improved with the introduction of Li ions. As the Li ion content increased, the material strength and toughness showed a trend of first increasing and then decreasing. HPU2-1:2 in Example 2 exhibited the highest strength and toughness, but when the Li ion content was too high, both the strength and toughness of the material were lower than those of HPU2 in Comparative Example 1. It is worth noting that the maximum tensile strength of Example 1 was much higher than that of Comparative Example 1, and the elongation at break was slightly higher; the maximum tensile strength of Example 2 was much higher than that of Comparative Example 1, and the elongation at break was lower; while the elongation at break of Example 3 was much higher than that of the Comparative Example, but the maximum tensile strength and toughness were slightly lower than those of Comparative Example 1. Therefore, through reasonable introduction of Li ions, the materials in these examples all exhibited exceptional mechanical properties, namely high mechanical strength, high tensile strength, and high toughness. Significantly different mechanical properties were obtained by changing the Li ion content. Therefore, materials that can meet different application needs can be obtained in this way. For example, HPU2-1:2 can be used when higher mechanical strength is required, and HPU2-1:3 can be used when higher tensile strength is required.
[0101] Depend on Figure 4As shown in Table 1, Example 2 exhibits the highest strength and toughness compared to Examples 4 and 5. The ratio of Li ions to UPy is the same in all three examples (2:1), the difference being the amount of UPy. Since the present invention coordinates Li ions with UPy, the mechanical properties of the polyurethane material can be controlled simply by changing the UPy content. This indicates that the present invention provides more ways to control the mechanical properties of polyurethane materials, thereby enabling the acquisition of materials suitable for a wider range of applications.
[0102] The polyurethane materials prepared by the method provided in this invention are rich in coordination bonds, offering various ways to improve the strength and toughness of polyurethane materials. Specifically, the polyurethane elastomers containing UPy and lithium ion coordination prepared in Examples 1 to 5 all exhibit mechanical properties comparable to or even superior to traditional polyurethanes. This is mainly due to the dynamic crosslinking system formed by the synergistic coordination of UPy quadruple hydrogen bonds and lithium ion multiple coordination in the network. These non-covalent crosslinking points can reversibly dissociate and reconstruct during stress, forming an efficient reversible energy-dissipating network within the structure. Furthermore, the metal-ligand coordination bonds formed between lithium ions and UPy carbonyl oxygen, pyrimidine nitrogen, and other sites, as well as the ion-dipole interaction between lithium ions and soft-segment ether oxygen, have strong non-covalent bonding forces. During molecular chain slip and bond breaking, a large amount of energy is dissipated, thus significantly toughening the material. Compared to relatively weak supramolecular interactions such as simple quadruple hydrogen bonds and π-π stacking, the coordination and ion cluster effects involving lithium ions exhibit higher apparent bond energies and synergistic stability. The complexation of UPy with lithium ions in the polymer matrix induces the generation of ion-rich microregions, forming nano-sized lithium-UPy ion clusters. These clusters are uniformly dispersed in the soft polyether / polyester network domains, acting as high-strength physical cross-linking centers and greatly enhancing network integrity.
[0103] In addition, the electrochemical performance of the sample from Example 2 was tested. The testing standard was GB / T 28817-2022; the test environment was 25℃.
[0104] Figure 5 The AC impedance spectroscopy curve of the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions prepared in Example 2 of this invention. Figure 5 As can be seen, the sample HPU2-1:2 in Example 2 exhibits excellent ionic conductivity. The fitted resistance (equivalent resistance of the Nyquist plot of the AC impedance spectroscopy) of HPU2-1:2 is approximately 162.1 Ω, and its low bulk resistance enables the material to possess good conductivity. Therefore, the results of the AC impedance spectroscopy experiment fully demonstrate that the Li ion-coordinated polyurethane elastomer prepared in this invention not only exhibits high strength, high toughness, and high stretchability, but also has excellent conductivity, and is expected to be used in extreme conditions or complex environments.
[0105] In summary, this invention designs and constructs a linked polymer network that integrates UPy quadruple hydrogen bonds with lithium-ion coordination, effectively combining supramolecular dimerization, ionic crosslinking, and chain entanglement effects at a single node. Compared to Comparative Example 1, which contains only UPy without lithium salt, the lithium-coordinated UPy polyurethane of this invention combines the advantages of both supramolecular hydrogen bond networks and dynamic ionic crosslinking. The coordination electrostatic association between lithium ions and UPy acts as a "sacrificial physical crosslink" under external tension, preferentially dissociating and dissipating a large amount of strain energy, while the UPy dimer hydrogen bonds maintain the basic network shape, thereby synergistically improving the tensile strength, ductility, and toughness of the material. Simultaneously, in the prepared lithium-ion UPy polyurethane, lithium coordination units construct strong ion-coordination electrostatic interactions within the material. This dynamic interaction differs from traditional hydrogen bonds and van der Waals forces, exhibiting higher bonding strength and tunability / reversibility, endowing the material with outstanding toughness and energy dissipation characteristics. Therefore, it exhibits higher ductility and more significant mechanotropic energy dissipation than a simple hydrogen-bonded physical network, which stems from the dynamic sacrifice and recombination kinetics of the lithium coordination structure. Furthermore, with the introduction of lithium-ion-UPy coordination crosslinking structures, lithium-containing polyurethane materials show significant improvements in various mechanical properties such as tensile strength, elongation at break, and toughness.
[0106] The results show that ion coordination can effectively combine dynamic properties and good stability, making it a promising new type of functional polymer material.
[0107] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention. The above embodiments are provided only for the purpose of describing the present invention and are not intended to limit the present invention. Parts not described in detail in this specification are well-known in the art and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. All equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be covered within the scope of the present invention.
Claims
1. A polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions, characterized in that, In the polyurethane material based on the synergistic coordination of ureidinone and lithium ions, ureidinone units are grafted onto the polyurethane molecular chain. The ureidinone units and lithium salt together construct a multi-dynamic interaction network. The ureidinone units can form a dimer structure with high-strength non-covalent crosslinking points through self-recognizing quadruple hydrogen bonds. The lithium ions in the lithium salt undergo metal-ligand coordination with the coordination sites on the ureidinone and generate ion-dipole interactions with the ether oxygen in the soft segment. The multi-dynamic interaction network is a linked dynamic network integrating hydrogen bonds and metal-ligand coordination. The polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions forms a microphase separation structure in its molecular structure, which includes a hard phase and a soft phase; wherein the hard phase is a ureidopyrimidinone-lithium ion aggregate, and the hard phase is a multifunctional nanodomain with both rigidity and conductivity. The soft phase is composed of polyether or polyester segments and serves as a continuous channel for lithium-ion transport.
2. The method for preparing the polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions as described in claim 1, characterized in that, Includes the following steps: S1: Add a first chain extender to the polyurethane prepolymer to carry out a first chain extension reaction; wherein the first chain extender is a diamine chain extender or a diol chain extender, and the molar ratio of the first chain extender to the polyol in the polyurethane prepolymer is (1~2):4; the reaction temperature of the first chain extension reaction is 60-100℃, and the reaction time is 1h~12h. S2: After the first chain extension reaction is completed, a second chain extender is added to carry out a second chain extension reaction; wherein the second chain extender is ureidopyrimidinone, and the molar ratio of the second chain extender to the polyol in the polyurethane prepolymer is (1~3):4; the reaction temperature of the second chain extension reaction is 60-100℃, and the reaction time is 3h~12h; S3: After the second chain extension reaction is completed, lithium salt is added to carry out the reaction; wherein the molar ratio of the second chain extender to lithium salt is 1:1~3; the reaction temperature in step S3 is 60-100℃, and the reaction time is 3h~12h. S4: After the reaction is completed, the reaction product obtained in step S3 is subjected to film formation and drying treatment to obtain a polyurethane material based on the synergistic coordination of ureidopyrimidinone and lithium ions.
3. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 2, characterized in that, The first chain extender is adipic acid dihydrazide.
4. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 3, characterized in that, The second chain extender is 1-(6-(3-(1,3-dihydroxy-2-methylprop-2-yl)ureido)hexyl)-3-(4-methyl-6-oxo-1,6-dihydropyrimidin-2-yl)urea.
5. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 4, characterized in that, The lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
6. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 5, characterized in that, Steps S1, S2 and S3 are all carried out under the condition of an inert reaction gas.
7. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 6, characterized in that, In step S4, the drying temperature is 60℃~100℃ and the drying time is 24h~72h.
8. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 7, characterized in that, When the first chain extender, the second chain extender, or the lithium salt is a solid, the solid should be dissolved first before being added to the corresponding reaction system.
9. The method for preparing polyurethane materials based on the synergistic coordination of ureidopyrimidinone and lithium ions according to claim 8, characterized in that, The polyurethane prepolymer in step S1 is prepared by the following steps: Polyurethane prepolymer is obtained by mixing polyol, diisocyanate and solvent, adding catalyst and carrying out prepolymerization reaction.
Citation Information
Patent Citations
Self-healing polymer and preparation method and application thereof
CN110437456A
Polyurethane and preparation thereof, supramolecular polyurethane elastomer and preparation and application thereof
CN114752036A